THE EFFECT OF EXCLUSIVE BREASTFEEDING ON BABY GROWTH AT KAKAIT VILLAGE, GUNUNG SARI SUB-DISTRICT - Yunita Marliana (poltekkes kemenkes mataram, 2017)
Abstract : UNICEF and WHO recommend that children should be breastfed for at least 6 months. (IDAI, 2008). Children are the next generation of Nation. Superior children support the future of Nation to better conditions. One of the factors that affects the quality of children is their optimally growth. The best infants’ nutrition in their early age is breastfeeding (Soetjiningsih and Ranuh, 2013). The research design was observational analytic. The population was 62 infants whose age 6-12 months and there were 54 respondents as the sample in the study. The sample used non probability sampling technique with purposive sampling method. This research was conducted at Kekait village, Gunung Sari sub-district. Based on the research result was obtained most of the characteristics based on age around 20-35 years was 90.7%, Elementary School was 53.7%, a number of children 2-4 was 64.8% and the job as a housewife was 64.8%. Chi-Square test indicated 0.000 thus it can be concluded there was a significant influence between exclusive breastfeeding on baby growth.